Intercultural responsiveness in the second language learning classroom - Jones, Kathryn, Ed (Advances in Educational Technologies and Instructional Design (AETID) book series, 2017)
"This book will aim to provide relevant theoretical frameworks and the latest empirical research findings on implementing Intercultural Responsiveness (IR) among second language learners. Jones (2013) defined Intercultural Responsiveness (IR) as a merging of multicultural awareness, intercultural sensitivity while cultural responsiveness is overlapping both along a cultural awareness continuum"--